Begging in Nigeria - Igbinovia, Patrick Edobor (International journal of offender therapy and comparative criminology, 1991)
Phenomenon of beggars in Nigeria is described. Classes and types of beggars indicate the complexity of this social problem. The author points to a variety of sources for this problem and suggests specific changes as steps toward alleviation